“Relief Necessary for the Orphaned Children”: Wet-Nurses for Foundlings in Vilnius in the Second Half of the Eighteenth Century - Jakulis, Martynas (Vilnius University Open Series, 2024)
The article focuses on the wet-nurses for foundlings in Vilnius in the second half of the eighteenth century when the number of children abandoned by their parents grew significantly. Wet-nurses who nursed foundlings have already received some attention in previous historiography, however, there have been no attempts to more thoroughly explore who were the women employed by hospitals and other charitable institutions as wet-nurses, what were the conditions of their employment, and how important could the income earned from this work have been in supporting their households. The research, based primarily on two distinct lists of foundlings and wet-nurses from 1789 and 1790 (see apendices), reveals that the wet-nurses were married Catholic women who had given birth several months earlier. The sources show that, throughout the second half of the eighteenth century, their monthly payment of 8 złotys remained unchanged despite inflation or other economic processes as well as the the increase in demand of women able and willing to work as wet-nurses for foundlings when the numbers of abandoned children grew significantly. Nevertheless, such employment provided women with, albeit low, but permanent and–if the nursling did not perish early–lasting income. The research demonstrates that at least some of the wet-nurses were married to artisans and merchants, and resided in Vilnius and its suburbs, not, as was usual in other European regions, the countryside, although there are indications in later sources that foundlings were actually placed with nurses of the surrounding countryside. The registers of baptisms and marriages reveal that at least some of these women were married, baptized their own children at the parish church of St John, and acted as godmothers to the children of other parishioners. However, the data on the social status of women employed as wet-nurses for foundlings is insufficient to confirm that–just like in other European cities–they were destitute and came from the lowest strata of society.